Survey on the availability, price and affordability of selected essential drug of non-communicable diseases in community pharmacy of Kathmandu Valley District. - Shrestha,Rajeev (2017)
ABSTRACT: Background: Essential medicines are intended to be available at all times in adequate amounts, in the appropriate dosage forms, with assured quality and adequate information, and at a price, the individual and the community can afford. The purpose of this study was to analyze the status of NCDs Essential medicines in Kathmandu valley districts by determining the availability, price, affordability and individual medicines manufacturer. Methodology: A cross-sectional allopathic community pharmacy based descriptive study carried out by non-probability quota sampling. A total 94 community pharmacies was surveyed and total eight NCDs essential medicine was assessed. The information regarding the NCDs essential medicine was collected by predesigned form. The data was analyzed by the use of minimum, maximum, mean, percentage, percentage variation and shown pictorially. Result: The availability of essential medicine was higher in NP/UMNP/MNP than VDC. There was no availability of beclomethasone 50 ug aerosol. There was no 100 % availability of essential medicine. There was high competitor and high price variation in metformin 500 mg (price variation 257.27%) and Atorvastatin 10 mg (Price Variation 327.63 %) comparison to other essential medicines. The study showed that the available majority of brands of Selected EM was manufactured by Nepal 54.04 % and second largest manufacturer was India. The study showed that the treatment for one month of Glibenclamide 5 mg, Metoformin 500 mg, Atenolol 50 mg, Enalapril 5 mg, Atorvastatin 10 mg, Hydrochlorothiazide 25 mg and Salbutamol 100 ug Aerosol was 0.1, 0.22, 0.22, 0.22, 0.60, 0.37 and 0.37 days of wages respectively. Conclusion: The availability of the essential medicine according to the essential medicine list 2011 is not uniform in all the regions. The essential medicine list was not revised according to the status of disease and pattern of drug utilization in particular disease. The country has not seen to be self-reliant in producing essential medicine although it has become major producer of essential medicine. Keyword: Non-communicable disease, community pharmacy, essential medicine